Media dan Kontribusinya dalam Internalisasi Nilai Pluralisme Agama di Indonesia - Al Mufti, Alex Yusron (Prodi Aqidah dan Filsafat Islam, Fakultas Ushuluddin, Universitas Islam Negeri Sunan Kudus, 2017)
This study aims to find out and to describe the media and its contribution in internalizing the value of religious pluralism in Indonesia. This article used a descriptive qualitative method, with the Research library approach. The finding showed that mass media in its role have two tendencies, 1) creating potential conflicts, and 2) religious pluralistic harmony and awareness. The mass media has a role to inform and educate the public about the reality of pluralism and plurality of religions in Indonesia. In plural society, mass media plays an important role in creating peaceful conditions. The contribution of the media should be directed to consider the public interest in creating peace conditions. The existence of mass media as reported through TV, radio and newspapers contributes to the internalization of the values of religious pluralism on the grounds that the mass media informs the public that the difference in Indonesia is a necessity. The implications of this are people will be able to recognize, accept and appreciate the differences that exist, whether differences in race, language, color, culture and religion.